P307 Demonstration of short-term plasticity in the dorsolateral prefrontal cortex with theta burst stimulation: A TMS-egg study. Issue 3 (March 2017) - Chung, S.W.; Lewis, B.P.; Rogasch, N.C.; Takashi, S.; Thomson, R.; Bailey, N.W.; Hoy, K.E.; Fitzgerald, P.B.
Abstract : Introduction: Repetitive transcranial magnetic stimulation has the unique ability to modulate cortical activity. In particular, theta burst stimulation (TBS) has gained notable attention due to its efficacy in short stimulation durations. Vast majority of TBS studies have demonstrated corticospinal excitability change, however we know very little about the effects of TBS on cortical excitability outside of the motor cortex. There is increasing interest in the use of TBS as a therapeutic tool for disorders such as depression and schizophrenia. In developing clinical applications in such psychiatric illnesses, there is a need to explore whether the same effects on corticospinal excitability are achieved in non-motor regions. Objectives: The study aimed to examine the effects of iTBS and cTBS on cortical excitability in the dorsolateral prefrontal cortex, a brain region relevant to the treatment of a number of neuropsychiatric disorders. We hypothesized that iTBS and cTBS protocol would increase and decrease cortical excitability respectively. Materials & methods: 10 healthy participants were stimulated with either iTBS, cTBS or sham on F3 electrode over 3 different sessions. TMS-EEG was used to assess cortical excitability change via TMS-evoked potentials (TEPs) and TMS-evoked oscillations. Results: Analysis on F3 revealed increase in N120 amplitude ( p  = .009) from pre to post iTBS. Cluster-based statistics showed one significant negative cluster at N120 ( p  = .003), indicating increased amplitude at the site of stimulation and contralaterally. TBS-induced changes (post - pre) were calculated and compared among different TBS conditions. N120 amplitude post iTBS was higher than cTBS at F3 ( p  = .042). TMS-evoked oscillations were significantly increased after iTBS in theta frequency at F3 from 50 to 250 ms ( p  = .044). TMS-evoked oscillations among different TBS at F3 yielded higher theta power after iTBS compared to cTBS and sham ( p  < .05; Fig. 1). Conclusion: This study provides some of the first evidence that TBS produces direct changes in cortical excitability in the prefrontal cortex. This may be a useful approach to optimise stimulation paradigms prior to the conduct of clinical trials.